2018
DOI: 10.3389/fphar.2018.01132
|View full text |Cite
|
Sign up to set email alerts
|

The Extent and Reasons for Dissatisfaction From Outpatients Provided With Pharmacy Services at Two Public Hospitals in Eastern Ethiopia

Abstract: Background: Satisfaction of patients for pharmaceutical services reflects their preferences and expectations, and the realities of care. It is critical to understand the extent of dissatisfaction for pharmaceutical services and its associated factors in order to optimize the required quality of the services provided. Therefore, this study is aimed to explore the extent and reasons for dissatisfaction from outpatients provided with the pharmacy services at Hiwot Fana Specialized University Hospital and Federal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 26 publications
3
24
1
Order By: Relevance
“…These studies vary in methodological aspects and study population which precludes the direct comparison of our findings with them. However, low level of satisfaction in the current study is comparable to international surveys [ 1 , 17 – 19 ]. The global criteria to measure the patient satisfaction varies markedly.…”
Section: Discussionsupporting
confidence: 73%
“…These studies vary in methodological aspects and study population which precludes the direct comparison of our findings with them. However, low level of satisfaction in the current study is comparable to international surveys [ 1 , 17 – 19 ]. The global criteria to measure the patient satisfaction varies markedly.…”
Section: Discussionsupporting
confidence: 73%
“…Two studies revealed that dispensers' inadequate knowledge was found to be a statistically significant predictor for satisfactory counseling. 19,24 Lack of updated drug information was reported in four studies (39.7-90%) as 1298 the major barrier for patient-pharmacist interaction. The educational status of pharmacy professionals was also a significant determinant.…”
Section: Discussionmentioning
confidence: 99%
“…The absence or limited applicability of the medicines regulatory framework distorts the execution of all regulatory functions required for effective medicine regulation. 19 Although only one of the reviewed studies reported that the availability of prescribed medications was a factor for 38.9% patient-pharmacy professional interactions, in many poor African countries, 50-60% of the population lack access to medications. 44 The overall average availability of essential medicines was 91% in Gonder 45 and 55.65% in South West Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that waiting time for pharmaceutical services is still one of the causes of patient dissatisfaction. Dissatisfaction with pharmaceutical services is influenced by several factors, including marital status and the education level of respondents (Nigussie & Edessa, 2018).…”
Section: Laumentioning
confidence: 99%